2007
DOI: 10.1111/j.1468-2982.2007.01432.x
|View full text |Cite
|
Sign up to set email alerts
|

Medication Overuse Headache: Clinical Features Predicting Treatment Outcome at 1-Year Follow-Up

Abstract: We present a prospective study of 240 patients with medication overuse headache (MOH) treated with drug withdrawal and prophylactic medications. At 1-year follow-up, 137 (57.1%) patients were without chronic headache and without medication overuse, eight (3.3%) patients did not improve after withdrawal and 95 (39.6%) relapsed developing recurrent overuse. Age at time of MOH diagnosis, regular use of benzodiazepines, frequency and Migraine Disability Assessment (MIDAS) score of chronic headache, age at onset of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
98
2
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(117 citation statements)
references
References 23 publications
(45 reference statements)
14
98
2
3
Order By: Relevance
“…Our study shows in agreement with a recent publication [23] that outcome after withdrawal therapy is not related to headache diagnosis. Pini et al [24] found that patients overusing only one drug had a more favourable outcome than patients overusing more than one.…”
Section: Discussionsupporting
confidence: 95%
“…Our study shows in agreement with a recent publication [23] that outcome after withdrawal therapy is not related to headache diagnosis. Pini et al [24] found that patients overusing only one drug had a more favourable outcome than patients overusing more than one.…”
Section: Discussionsupporting
confidence: 95%
“…Many researchers pointed out the severity of baseline migraine as source of the main outcome predictors [12,20]. However, long-term prospective studies were not equally encouraging, indicating that few or none of the baseline characteristics significantly influenced the outcome measures [11].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest predictors of relapse after a successful detoxification in samples of chronic migraineurs with MO [1,12,[19][20][21][22]. However, in tertiary centers, these putative factors are present and severe to such an extent that they could reciprocally influence each other and blur the clinical presentation and the physician manageability.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding relapse, recent studies indicate that the highest risk is in the first 12 months, although different percentages are reported by various authors (22-44 % in Trucco et al [41]; 60-75 % in Zidverc et al [42] and Baumgartner et al [43]; or 40-60 % in Andrasik [15], Katsarava [44], Hagen et al [45], and Fritsche et al [46]). The risk decreases, however, if medication overuse is avoided for 12 months after withdrawal, and in general, MOH treatment is considered successful if the improvement obtained after withdrawal/detoxification with or without prophylaxis is maintained at 1-year follow-up [42,[47][48][49][50][51]. Several factors are considered a risk for relapse: male sex, a diagnosis of tension-type headache or mixed headache, frequency of the primary headache, higher severity of the migraine condition, long duration of drug overuse, greater number of previous prophylactic treatments, intake of combination analgesic products (e.g., one or more NSAIDs with caffeine or codeine) or of codeine-containing drugs, ergotamine or triptan withdrawal more than analgesic withdrawal, use of the same drug that has caused overuse, lower improvement after drug withdrawal, reduced sleep quality, and high levels of body pain and of disability score for chronic headache [12].…”
Section: Ichd-3 Beta 2013mentioning
confidence: 92%
“…The short-term response (2-month follow-up) to drug withdrawal in MOH has been suggested to be genetically determined [40]. Regarding relapse, recent studies indicate that the highest risk is in the first 12 months, although different percentages are reported by various authors (22-44 % in Trucco et al [41]; 60-75 % in Zidverc et al [42] and Baumgartner et al [43]; or 40-60 % in Andrasik [15], Katsarava [44], Hagen et al [45], and Fritsche et al [46]). The risk decreases, however, if medication overuse is avoided for 12 months after withdrawal, and in general, MOH treatment is considered successful if the improvement obtained after withdrawal/detoxification with or without prophylaxis is maintained at 1-year follow-up [42,[47][48][49][50][51].…”
Section: Ichd-3 Beta 2013mentioning
confidence: 97%